BO‘LAJAK O‘QITUVChILARDA IJTIMOIY-MADANIY KOMPETENTLIKNI RIVOJLANTIRIShNING TARIXIY ASOSLARI HAMDA IJTIMOIY-PEDAGOGIK OMILLARI - Xolmirzayev, N. (SCIENCE and SOCIETY, 2025)
The article analyzes the historical foundations of the development of socio-cultural competence in future teachers, the state of study of socio-cultural competence, the components of socio-cultural competence, the historical pedagogical factors of the development of socio-cultural competence in future teachers based on ensuring and generalizing the interrelationship of historical, cultural, and national foundations.
Keywords: national value; self-awareness; higher education; future teacher; competence; socio-cultural competence; social activism; oriental scholars; components of socio-cultural competence; development of socio-cultural competence